Silver Box and Bracelets - G.F. MacDonald Collection (1972)
Silver bracelet. beaver design belonging to Frog clan. Silver Box. Killer whale and wolf designs. Created by Earl Muldoe. Art works created by students of the Gitanmaax School of Northwest Coast Indian Art located at the 'Ksan Historical Village.